Portrait of Equality, Justice, and Humanitarian Crisis in Scopus Database: A Bibliometric Study - Hudaa, Syihaabul; Ying, Luo; D'Agustino, Matteo (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2024)
Equality, justice, and humanitarian crises are complex issues for people worldwide. These issues have always interested researchers worldwide and have been published in the Scopus database. The purpose of writing this article is to analyze articles that have been published in the Scopus database. Researchers try to find exciting research throughout the year using keywords in research that are trending research topics. This research is included in a literature study using descriptive qualitative analysis. Researchers traced the keywords in this study: equality, justice, and humanitarian crises, then collected them in CSV files. The collected data was analyzed using bibliometric analysis using bibliophily. It was found that authors from the Americas and Europe dominate the Scopus database. In addition to the authors, the journals that published the issue were from the Americas and Europe. The topics researchers are talking about from the results of bibliometric mapping include human and humanitarian crises, war, mental health, military intervention, migration, and others.